2022
DOI: 10.1017/s0047279421000799
|View full text |Cite
|
Sign up to set email alerts
|

The Leadership of Co-Production in Health and Social Care Integration in Scotland: A Qualitative Study

Abstract: The involvement of citizens in the production and creation of public services has become a central tenet for administrations internationally. In Scotland, co-production has underpinned the integration of health and social care via the Public Bodies (Joint Working) (Scotland) Act 2014. We report on a qualitative study that examined the experiences and perspectives of local and national leaders in Scotland on undertaking and sustaining co-production in public services. By adopting a meso and macro perspective, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…To this end, more work needs to be done to create a ‘national lever’ that clarifies complementary roles and lines of responsibility needed to provide the necessary political and social basis for building a coherent mental health agenda. 25 …”
Section: Discussionmentioning
confidence: 99%
“…To this end, more work needs to be done to create a ‘national lever’ that clarifies complementary roles and lines of responsibility needed to provide the necessary political and social basis for building a coherent mental health agenda. 25 …”
Section: Discussionmentioning
confidence: 99%
“…A key challenge at the start of any initiative employing co-design and co-production as methods of engagement is to define exactly what such approaches are both theoretically and in practice. Connolly et al, (2022) explored the meanings given to such approaches to stakeholder engagement in a review of co-production and co-design efforts in Scotland. They wanted to find out if there was firm evidence that such approaches could support the integration of health and social care services and if such efforts resulted in sustainable activity.…”
Section: Co-design and Co-production As A Framework For Community Actionmentioning
confidence: 99%
“…They wanted to find out if there was firm evidence that such approaches could support the integration of health and social care services and if such efforts resulted in sustainable activity. Connolly et al, (2022) concluded that co-design and co-production as approaches to achieving broad engagement across stakeholder groups have diverse meanings across different professional and practice contexts. Often these approaches were employed with no specific underlying theory or coherent framework, co-design and co-production were simply assumed to entail a "joint effort" and be regarded as offering unquestionable benefits (Connolly et al, 2022, p. 7).…”
Section: Co-design and Co-production As A Framework For Community Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sector co-production involving volunteers in the production and delivery of public services has come to the forefront of many advanced welfare states across Europe and elsewhere (Voorberg et al, 2015;Brandsen & Verschuere, 2018;Connolly et al, 2022). Increasing pressure on public welfare economies has led to a new agenda of increased nonprofit and voluntary involvement in welfare policy fields, such as elderly care, childcare, labour market activation, and integration of refugees and immigrants (Christensen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%